(untitled) (Boletin Médico de Postgrado, 2020)
Welfare in hospitalized children is a challenge for medical sciences. With the aim to determine psychosocial risk factors that affect behavior in schoolchildren hospitalized in the Intermediate Care Unit of the Servicio Desconcentrado Hospital Pediátrico Dr. Agustín Zubillaga, a descriptive transversal study was carried out in 60 schoolchildren hospitalized in February 2019. The sample consisted of predominantly female schoolchildren with an average age of 11 years old, with acute disease and a hospital stay > 7 days, with easy temperament that did not change during hospitalization, medium level of self-control and a dependency behavior expressed as separation anxiety and fear of unknown people. Overprotection with low parental stress was observed. A good interaction with health personnel as well as collaboration (with fear) during medical procedures was present in most children. Parents manifested to be well informed about the health of their child. The presence of psychosocial risk factors during hospitalization should be recognized by health care services for its potential negative effect on behavior, mental and physical health of children.